2021
DOI: 10.1590/s1679-49742021000200007
|View full text |Cite
|
Sign up to set email alerts
|

Aleitamento materno exclusivo e introdução de alimentos ultraprocessados no primeiro ano de vida: estudo de coorte no sudoeste da Bahia, 2018

Abstract: Resumo Objetivo: Analisar a associação entre aleitamento materno exclusivo (AME) e a introdução de alimentos ultraprocessados em crianças menores de 12 meses. Métodos: Estudo de coorte, realizado com crianças de Vitória da Conquista, Bahia, Brasil. A exposição principal foi o AME (em dias: <120; 120-179; ≥180). A variável-desfecho do estudo foi a introdução de quatro ou mais tipos de ultraprocessados no primeiro ano de vida. Utilizou-se análise de regressão de Poisson. Resultados: Foram avaliadas 286 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
1
12
0
4
Order By: Relevance
“…In school-age children, the prevalence of wheezing diseases reached 87% of the cases, with the highest participation of these foods in the diet (29). Another study found no association between UPF consumption at 6 years of age with the presence of asthma and wheezing among adolescents, demonstrating the need for studies in other populations, mainly due to some limitations in the consumption analysis, as reported by the authors themselves (30).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In school-age children, the prevalence of wheezing diseases reached 87% of the cases, with the highest participation of these foods in the diet (29). Another study found no association between UPF consumption at 6 years of age with the presence of asthma and wheezing among adolescents, demonstrating the need for studies in other populations, mainly due to some limitations in the consumption analysis, as reported by the authors themselves (30).…”
Section: Discussionmentioning
confidence: 90%
“…This greatest participation of UPF was observed in studies that analyzed infants diets (21,(24)(25)(26)(27)(28)(29)(30)32), representing up to 70% of calories consumed by children older than 1.5 years (21) which is much higher than the average found in pregnant women (22.6%) and lactating women (16%).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A participação de alimentos ultraprocessados vem crescendo ao longo dos anos, nos domicílios das famílias brasileiras. A oferta desses alimentos não é recomendada nos primeiros anos de vida, por eles causarem impactos negativos à saúde no curto ou longo prazo (Porto et al, 2018).…”
Section: Resultsunclassified